Myco-Synergism Boosts Herbivory-Induced Maize Defense by Triggering Antioxidants and Phytohormone Signaling - Batool, Raufa; Umer, Muhammad Jawad; Wang, Yangzhou; He, Kanglai; Shabbir, Muhammad Zeeshan; Zhang, Tiantao; Bai, Shuxiong; Chen, Jie; Wang, Zhenying (Frontiers in Plant Science, 2022)
Background: Biocontrol strategies are the best possible and eco-friendly solution to develop resistance against Ostrinia furnacalis and improve maize yield. However, knowledge about underlying molecular mechanisms, metabolic shifts and hormonal signaling is limited. Methods: Here in, we used axenic and consortium of entomopathogenic Beauveria bassiana OFDH1-5 and pathogen-antagonistic Trichoderma asperellum GDFS1009 in maize and observed that consortium results in higher chlorophyll and antioxidants with a decrease in O. furnacalis survival. We performed a comprehensive transcriptome and untargeted metabolome profiling for the first time at vegetative stage in fungal inoculated maize leaves at 0-, 12-, 24-, 48-, and 72-h post insect infestation. Results: A total of 130 Negative and 491 Positive metabolomic features were detected using UHPLC-QTOF-MS. We identified 13 candidate genes not reported previously via Weighted Gene Co-expression Network analysis (WGCNA) highly correlated with JA-ET signaling pathway and antioxidants. Intramodular significance and RT-qPCR expressions showed that these genes are the true candidate genes. Consortium resulted in High JA, SA, and ET content in plants. Conclusion: we assumed that defense against ACB attack is under the influence of multiple genes at the same time. Our results provide insights into the genetics, biochemicals and metabolic diversity and are useful for future biocontrol strategies against ACB attack.